The Tyranny of Time in Capitalist Society: Moishe Postone and the Abstract Temporal Domination of Capital - Vargas Muñoz, Roberto (2025)
The article identifies and discusses some of Moishe Postone’s main theses on the critique of traditional Marxism and the critique of capitalism as a modern mode of social life through his reinterpretation of late Marx. He then explores the conceptualisations of immanent critique, abstract domination and abstract time. To conclude, he describes some of the relevant criticisms of the author and raises two considerations about the concept of abstract time.